The Western World Daily Readings on Geography - Quam, Joel; Campbell, Scott; Open Textbook Library (Open Textbook Library, 2020)
In essay format, this textbook considers examples of various sub-categories of Geography in combination with five regions of the Western World.
1. What is the Western World? -- 2. What is Regional Geography? -- 3. Cultural Geography -- 4. Economic Geography -- 5. Historical Geography -- 6. Physical Geography -- 7. Political Geography -- 8. Population Geography -- 9. Urban Geography -- 10. Medical Geography -- 11. Pacific Realm -- 12. Pacific Realm: Regional Example -- 13. Pacific Realm: Cultural Geography I -- 14. Pacific Realm: Economic Geography I -- 15. Pacific Realm: Historical Geography I -- 16. Pacific Realm: Physical Geography I -- 17. Pacific Realm: Political Geography I -- 18. Pacific Realm: Population Geography I -- 19. Pacific Realm: Urban Geography I -- 20. Pacific Realm: Cultural Geography II -- 21. Pacific Realm: Economic Geography II -- 22. Pacific Realm: Historical Geography II -- 23. Pacific Realm: Physical Geography II -- 24. Pacific Realm: Political Geography II -- 25. Pacific Realm: Population Geography II -- 26. Pacific Realm: Urban Geography II -- 27. Pacific Realm: Overview -- 28. North America -- 29. North America: Regional Example -- 30. North America: Cultural Geography I -- 31. North America: Economic Geography I -- 32. North America: Historical Geography I -- 33. North America: Physical Geography I -- 34. North America: Political Geography I -- 35. North America: Population Geography I -- 36. North America: Urban Geography I -- 37. North America: Medical Geography I -- 38. North America: Cultural Geography II -- 39. North America Economic Geography II -- 40. North America: Historical Geography II -- 41. North America: Physical Geography II -- 42. North America: Political Geography II -- 43. North America: Population Geography II -- 44. North America: Urban Geography II -- 45. North America: Overview -- 46. Europe -- 47. Europe: Regional Example -- 48. Europe: Cultural Geography I -- 49. Europe: Economic Geography I -- 50. Europe: Historical Geography I -- 51. Europe: Physical Geography I -- 52. Europe: Political Geography I -- 53. Europe: Population Geography I -- 54. Europe: Urban Geography I -- 55. Europe: Cultural Geography II -- 56. Europe: Economic Geography II -- 57. Europe: Historical Geography II -- 58. Europe: Physical Geography II -- 59. Europe: Political Geography II -- 60. Europe: Population Geography II -- 61. Europe: Urban Geography II -- 62. Europe: Overview -- 63. Latin America and the Caribbean (LACAR) -- 64. Latin America and the Caribbean (LACAR): Regional Example -- 65. Latin America and the Caribbean (LACAR): Cultural Geography I -- 66. Latin America and the Caribbean (LACAR): Economic Geography I -- 67. Latin America and the Caribbean (LACAR): Historical Geography I -- 68. Latin America and the Caribbean (LACAR): Physical Geography I -- 69. Latin America and the Caribbean (LACAR): Political Geography I -- 70. Latin America and the Caribbean (LACAR): Population Geography I -- 71. Latin America and the Caribbean (LACAR): Urban Geography I -- 72. Latin America and the Caribbean (LACAR): Cultural Geography II -- 73. Latin America and the Caribbean (LACAR): Economic Geography II -- 74. Latin America and the Caribbean (LACAR): Historical Geography II -- 75. Latin America and the Caribbean (LACAR): Physical Geography II -- 76. Latin America and the Caribbean (LACAR): Political Geography II -- 77. Latin America and the Caribbean (LACAR): Population Geography II -- 78. Latin America and the Caribbean (LACAR): Urban Geography II -- 79. Latin America and the Caribbean (LACAR): Overview -- 80. Russian Domain -- 81. Russian Domain: Regional Example -- 82. Russian Domain: Cultural Geography I -- 83. Russian Domain: Economic Geography I -- 84. Russian Domain: Historical Geography I -- 85. Russian Domain: Physical Geography I -- 86. Russian Domain: Political Geography I -- 87. Russian Domain: Population Geography I -- 88. Russian Domain: Urban Geography I -- 89. Russian Domain: Cultural Geography II -- 90. Russian Domain: Economic Geography II -- 91. Russian Domain: Historical Geography II -- 92. Russian Domain: Physical Geography II -- 93. Russian Domain: Political Geography II -- 94. Russian Domain: Population Geography II -- 95. Russian Domain: Urban Geography II -- 96. Russian Domain: Overview -- 97. Russian Domain: Physical Geography III -- 98. North America: Cultural Geography III -- 99. Europe: Population Geography III -- 100. Latin America and the Caribbean (LACAR): Political Geography III --
In English.
Description based on print resource
Keywords: Social sciences -- Textbooks; Geography -- Textbooks; Humanities -- Textbooks; Rhetoric -- Textbooks